Dynamic muscle paralytic effects of a novel botulinum toxin A free of neurotoxin‐associated proteins - Wu‐chao Liu; Jun‐hui Su; Ya Feng; Xue‐rui Xiang; Li‐zhen Pan; Ying Liu; Lin Ma; Zhi‐yu Nie; Xue‐ping Zhang; Ling‐jing Jin (Wiley, 2022)
Abstract Structurally, botulinum toxin type A (BTX‐A) is composed of neurotoxin and nontoxic complexing proteins (CPs), and the neurotoxin has the function of blocking acetylcholine release from the neuromuscular junction and therefore paralyzing muscles. Nowadays, a novel botulinum toxin A free of CPs (chinbotulinumtoxin A, A/Chin) is produced, and the present study comprehensively evaluated the dynamic paralytic effect of A/Chin on the gastrocnemius muscle of rats. Different doses (0.01, 0.1, 0.5, 1, 2, and 4 U) of A/Chin and other BTX‐As with and without CPs were administered to the gastrocnemius muscles of rats and muscle strength was measured and compared at different postinjection timepoints (from day 0 to 84). With the dose increased, time‐to‐peak paralytic effect of other BTX‐As varied from day 3 to day 14, while A/Chin groups showed rapid and steady time to peak on day 3. At the lowest dose of 0.01 U, A/Chin showed significantly better peak paralytic effect than the others on day 3. When the dose increased to 0.5 U and more, A/Chin group also showed significant paralytic effect when the paralytic effect of other BTX‐As was worn off. Moreover, the paralytic effect of A/Chin was confirmed as muscle atrophy while hematoxylin-eosin staining was performed. In conclusion, compared with other BTX‐As, A/Chin showed rapid and steady time‐to‐peak paralytic effect and long‐term paralytic efficacy at the same dose level. And it might lay a solid foundation for further wide application of A/Chin in both clinical and cosmetic areas.